Catastrophic Left Ventricular Thrombosis Complicating Extra-corporeal Membrane Oxygenation: A Case Report - Pořízka, Michal; Kopecký, Petr; Mikulenka, Vladimír; Kunstýř, Jan; Lipš, Michal; Balík, Martin (Prague medical report, 2017)
A massive left ventricular thrombosis represents a rare however, catastrophic complication of a central veno-arterial extra-corporeal membrane oxygenation. We report a case of such complication in a patient with severe left ventricular dysfunction after cardiac surgery. Its management and preventive measures are described and discussed.
Keywords: Shock, Cardiogenic; obstrukce výtoku ze srdeční komory; Ventricular Dysfunction, Left; Extracorporeal Membrane Oxygenation; Extra-corporeal membrane oxygenation; Humans; koronární trombóza; Fatal Outcome; Cardiac Surgical Procedures; kardiochirurgické výkony; fatální výsledek; mimotělní membránová oxygenace; mužské pohlaví; Ventricular Outflow Obstruction; Heart failure; Cardiac surgery; kardiogenní šok; Coronary Thrombosis; Thrombosis; lidé; dysfunkce levé srdeční komory; Aged; senioři; Male